Analisis Sistem Informasi Akuntansi Pembelian dan Persediaan pada PT. XYZ - Juwitasary, Hanny; Martani, Marlene; Putra, Arya Nata Gani (Bina Nusantara University, 2015)
Company faces a business competition that requires the company to survive or be superior to its competitors. PT. XYZ is a trading company engaged in distribution of raw materials and goods of Japanese foodand it needs the support of Accounting Information Systems (AIS) to be applied in all business processes. One of the most important business processes is purchasing and supplying of raw materials. Raw material is a resourceor materials that have a good economic value to be sold directly or processed into finished goods that will be marketed. Therefore, it is important for companies to know how to do a good internal control related to thepurchase and inventory. The methodology used in this research is to conduct a survey on the condition of the company's business processes, the study of literature with the method of analysis and design of Object-Oriented Analysis and Design (OOAD). The results of this study is the analysis and design of purchases accounting information systems, cash expense and inventory that can assist the companies in carrying out business activities and organizing internal control related to the purchase and inventory and to be able to reduce the distortionsthat occur and to maintain the smooth operation of the company. The information systems that are designed are able to help the companies in reducing errors caused by data record error transactions by employees and allow the companies to control the supply of goods.